1999
DOI: 10.1159/000022497
|View full text |Cite
|
Sign up to set email alerts
|

Conjectures and Refutations on the Mode of Action of Heparins

Abstract: Low-molecular-weight heparins (LMWHs), like unfractionated heparin (UFH), exert their action primarily by accelerating the interaction between antithrombin (AT) and thrombin. At the levels of aXa activity that are attained in human pharmacology, it does not cause significant (>15%) inhibition of the clotting system. The essential differences between LMWHs and UFH are: (a) LMWHs attain higher plasma concentrations after subcutaneous injection (high bioavailability), and (b) in contrast to LMWHs, UFH contains ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In contrast to UFH, it does not contain molecules with MW > 15 kDa, which on good grounds can be thought to be responsible for hemorrhagic complications. 13 Its specific aXa and aIIa activities are 10% higher than those of UFH. This indicates that during the production of MMWH the content of high-affinity material remains constant.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to UFH, it does not contain molecules with MW > 15 kDa, which on good grounds can be thought to be responsible for hemorrhagic complications. 13 Its specific aXa and aIIa activities are 10% higher than those of UFH. This indicates that during the production of MMWH the content of high-affinity material remains constant.…”
Section: Discussionmentioning
confidence: 97%
“…Hemker and colleagues 13,14 surmised that the main antithrombotic activity of a heparin would be localized in molecules with a definite aIIa activity and yet small enough to have high bioavailability. Moreover, experiments demonstrated that the aXa activity of heparin is only a partial expression of the therapeutic potential and that the antithrombotic effect improves with increasing chain length of heparin fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However concentrations of F X (120 nmol/L) are normally 6 times higher in plasma compared with F V (20 nmol/L). Thus, in the course of the thrombin generation process, F Va is the rate limiting factor (7). When the test plasma is prediluted sevenfold, and then substituted with F V to a normal concentration both these clotting factors will be present in equimolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, this effect of heparin is inversely influenced by two MWdependent parameters. Therefore, after s.c. administration, a heparin with high MW, but not containing so called extra large molecule (25), should exhibit the best TFPI releasing potency.…”
Section: Discussionmentioning
confidence: 99%